Effect of Peer Video Disaster Management on Knowledge, Attitude, and Skill Among Primary School Children in Bengkulu City - Buston, Erni; Efendi, Pauzan; Pardosi, Sariman; Yusniarita, Yusniarita; Laasara, Nurun (Media Publikasi Cendekia Indonesia, 2025)
Natural disasters are unpredictable events, and preparedness is crucial to mitigate associated risks. One high-risk population for natural disasters is children. Disaster management programs for primary students is important to reduce the risk and prevent the worst impact. This study aims to examine the effectiveness of the peer video on disaster management knowledge, attitude, and skill among primary students. The sample size of this study was 60 students, with 30 students in the intervention and 30 in the control. The intervention group was given the video of disaster management, and the control group was given the leaflet. There is a pretest and a posttest, and in between, there are four times interventions given. The results revealed the effectiveness of disaster management education with peer video to improve the knowledge, attitude, and skill among primary students in Bengkulu City. Earthquake disaster management education in Bengkulu City among primary students is effective to reduce the risk. Future studies can include more predictors of risk management